The effects of thyrotropin releasing hormone on measures of mood in normal women - Betts, T.A. (1976)
1 A double blind controlled trial of the psychotropic effects of thyrotropin releasing hormone (TRH) on normal women is described. 2 Single oral doses of this hormone, compared with identical placebo, had no effect on conventional measures of mood, but did cause definite effects as measured by clinical ethological observations of videotaped interviews.